PEMANFAATAN METODE STORYTELLING BERBASIS SASTRA LISAN UNTUK MENINGKATKAN LITERASI BAHASA DI SEKOLAH DASAR - Indah Sulmayanti; Zulfa Nindia; Retno Novita Sari; Nessy (Jurnal Bastra (Bahasa dan Sastra), 2025)
This study aims to examine the effectiveness of oral literature-based storytelling methods in improving language literacy in elementary schools. The background of this study is based on the low literacy skills of elementary school students in Indonesia, which is caused by the lack of interesting and contextual learning methods. Storytelling is seen as an approach that is able to develop students' language skills comprehensively, listening, speaking, reading, and writing, as well as instilling local character and cultural values. The method used in this study is descriptive qualitative with documentation study techniques from various journals, scientific articles, and digital sources. The results of the study show that oral literature-based storytelling is able to improve listening and speaking skills, enrich vocabulary, foster creativity, and increase students' interest in reading and writing. This approach also creates a fun and interactive learning atmosphere. In addition, digital storytelling also strengthens the effectiveness of this method through the use of technology such as animated videos, interactive audio, and other digital media. The integration of oral literature and modern technology makes learning more relevant to the needs and characteristics of today's students. This study recommends the development of a storytelling-based learning model to be widely applied in elementary schools, and encourages further research that examines the integration of this method in cross-subject learning.